Political Direction for the Sidoarjo Regency Long-Term Regional Development Plan RPJPD 2025–2045 - Muharram, Fajar (West Science Social and Humanities Studies, 2025)
This study examines the formulation of the vision, mission, and long-term policy direction outlined in the Preliminary Draft of the Regional Long-Term Development Plan (RPJPD) of Sidoarjo Regency for the period 2025–2045. This study uses a qualitative approach with the aim of exploring in depth various notes and recommendations on the substance of the Draft Regional Regulation (Ranperda) on the Long-Term Regional Development Plan (RPJPD) of Sidoarjo Regency for 2025–2045, This research analyzes the alignment of Sidoarjo’s development aspirations with national and provincial planning frameworks. The findings reveal that the vision Sidoarjo as an Inclusive, Competitive, Prosperous, and Sustainable Metropolitan Region demonstrates strong thematic consistency with both national and East Java provincial development agendas. Furthermore, the five missions outlined in the RPJPD provide a clear operationalization of the vision across governance, economic, human resource, infrastructure, and social domains. These strategic elements form the foundation for policy coherence and sustainable regional development. The study concludes that Sidoarjo's RPJPD is holistically structured and aligned with multi-level planning, ensuring integrated development over the next two decades.